Investigation of Cardioprotective Effect of 2, 4-thiazolidinedione Derivative Using HFD-STZ Fed Rats - Amin, Heli H; Patel, Nileshkumar Joitaram; Patel, Nikita; Patel, Dolar Govindbhai (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Myocardial infarction is a 2nd most important origin of universal death and after coronary revascularization, cardiovascular events occurs further a lot in subjects through DM: 3.5- as well as 2-fold fatality ranks correspondingly behind percutaneous coronary intervention or coronary bypass graft surgery. Objectives: The aim of an attendance research was to discover usefulness of 2, 4- thiazolidinedione derivatives lying on diabetic MI and HFD-STZ diabetic rats. Materials and Methods: In in-vivo investigation, Type-2 diabetes was elicited by higher fatty meal plus little dosage for streptozotocin and MI was provoked by LAD Coronary artery ligation model. The rats were divided into a variety of groups, including treatment groups (Composite An epalrestat, Composite B pioglitazone). And after 15 days of treatment a variety of factors were evaluated, i.e. serum glucose, total cholesterol, serum triglycerides, lipid profile antioxidant enzymes, ECG analysis, and Histopathological examination of heart were done. Results: In in-vivo investigation, levels of serum glucose, triglycerides, LDL level, LDH level, CK-MB, Troponin I, malondialdehyde (MDA), total cholesterol, infarct area, were considerably decreased in composite A and B treated animals. Whereas the HDL level, antioxidant enzymes, had drastically risen in composite, treated animals balanced to disease control rats. In ECG analysis ST elevation was restored in drug treated animals. Composite treated heart indicated mild congestion and inflammation in histopathological examination. Homogenate of drug treated animals indicated less apoptotic signals and nearer to normal animals. Conclusion: The treatment with Composite A and Composite B notably ameliorated the alterations in MI in a dose dependant manner.
Keywords: 2, 4-Thiazolidinedione; Myocardial infarction; Diabetic MI; Type-2 diabetes; LAD; Macrovascular complication